2021
DOI: 10.1101/2021.04.06.21254882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for increased breakthrough rates of SARS-CoV-2 variants of concern in BNT162b2 mRNA vaccinated individuals

Abstract: The SARS-CoV-2 pandemic has been raging for over a year, creating global detrimental impact. The BNT162b2 mRNA vaccine has demonstrated high protection levels, yet apprehension exists that several variants of concerns (VOCs) can surmount the immune defenses generated by the vaccines. Neutralization assays have revealed some reduction in neutralization of VOCs B.1.1.7 and B.1.351, but the relevance of these assays in real life remains unclear. Here, we performed a case-control study that examined whether BNT162… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 23 publications
2
89
0
2
Order By: Relevance
“…[27][28][29] Pfizer/BioNTech has recently issued a press release reporting high efficacy in a study with a small number of recipients of the mRNA BNT162b2 vaccine conducted in the same population; however, a report from Israel suggests increased breakthrough infection rates by B.1.351 in BNT162b2 vaccinated individuals. 30,31 Studies have demonstrated reduced neutralization titers against the full B.1.351 variant following mRNA-1273 vaccination, although levels are still significant and expected to be protective based on challenge studies in NHPs. 30,31 Despite this prediction of continued efficacy of mRNA-1273 against this key variant of concern (VOC), the magnitude and duration of vaccine mediated protection is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Pfizer/BioNTech has recently issued a press release reporting high efficacy in a study with a small number of recipients of the mRNA BNT162b2 vaccine conducted in the same population; however, a report from Israel suggests increased breakthrough infection rates by B.1.351 in BNT162b2 vaccinated individuals. 30,31 Studies have demonstrated reduced neutralization titers against the full B.1.351 variant following mRNA-1273 vaccination, although levels are still significant and expected to be protective based on challenge studies in NHPs. 30,31 Despite this prediction of continued efficacy of mRNA-1273 against this key variant of concern (VOC), the magnitude and duration of vaccine mediated protection is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Studies have demonstrated reduced neutralization titers against the full B.1.351 variant following mRNA-1273 vaccination, although levels are still significant and expected to be protective based on challenge studies in NHPs. 30,31 Despite this prediction of continued efficacy of mRNA-1273 against this key variant of concern (VOC), the magnitude and duration of vaccine mediated protection is still unknown. Moreover, a key related question is whether development of new mRNA vaccines to match the B.1.351 variant will enable enhanced neutralization responses and durability.…”
Section: Introductionmentioning
confidence: 99%
“…In (Jackson et al, 2020), we could read : «Last, codon optimization and modification of nucleotides have contributed to translation efficiency. For example, optimization of guanine and cytosine (GC) content can have a significant impact (Kudla et al, 2016) and has been well established with DNA vaccines ». (Kudla et al, 2016) detailed this « CG rich manufacturing technology » : « Mammalian genes are highly heterogeneous with respect to their nucleotide composition, but the functional consequences of this heterogeneity are not clear.…”
Section: 00481884mentioning
confidence: 99%
“…For example, optimization of guanine and cytosine (GC) content can have a significant impact (Kudla et al, 2016) and has been well established with DNA vaccines ». (Kudla et al, 2016) detailed this « CG rich manufacturing technology » : « Mammalian genes are highly heterogeneous with respect to their nucleotide composition, but the functional consequences of this heterogeneity are not clear. In the previous studies, weak positive or negative correlations have been found between the silent-site guanine and cytosine (GC) content and expression of mammalian genes.…”
Section: 00481884mentioning
confidence: 99%
“…10 The Pfizer/BioNTech BNT162b2 mRNA vaccine was reported to be less effective against B.1.351 than against non-B.1.351 variants based on a small analysis of breakthrough infections that were enriched for B.1.351 in Israel. 11 The efficacy of CoronaVac/Sinovac inactivated virus vaccine in Brazil, where 75% of infections were with the P.1 variant, was estimated at around 50% against symptomatic infection. 12…”
mentioning
confidence: 99%